Read, write and talk a practice to enhance comprehension - Goudvis, Anne.; Harvey, Stephanie (Portland, Me. : Stenhouse Publishers, 2006)
An intermediate grade reading workshop where students engage in real-world literacy to improve reading comprehension.
Presenters: Stephanie Harvey, Anne Goudvis.
Keywords: Reading (Primary); Reading comprehension -- Study and teaching (Primary)